Formative research methods for designing culturally appropriate, integrated child nutrition and development interventions: an overview. (31st October 2013) - Bentley, Margaret E.; Johnson, Susan L.; Wasser, Heather; Creed‐Kanashiro, Hilary; Shroff, Monal; Fernandez Rao, Sylvia; Cunningham, Melissa
Abstract : Nutritional and developmental insults in the first few years of life have profound public health implications, including substantial contributions to neonatal, infant, and early childhood morbidity and mortality, as well as longer term effects on cognitive development, school achievement, and worker productivity. Optimal development that can lead to the attainment of an individual's fullest potential, therefore, requires a combination of genetic capacity, adequate nutrition, psychosocial stimulation, and safe, clean physical environments. Researchers and policymakers have called for integrated child nutrition and development interventions for more than 20 years, yet there are only a handful of efficacy trials and even fewer examples of integrated interventions that have been taken to scale. While a critical component in the design of such interventions is formative research, there is a dearth of information in both the literature and policy arenas to guide this phase of the process. To move the field forward, this paper first provides an overview of formative research methods with a focus on qualitative inquiry, a description of the critical domains to be assessed (infant and young child feeding, responsive feeding, and child development), and currently available resources. Application of these methods is provided through a real‐world case study—the design of an integrated nutrition and child development efficacy trial in Andhra Pradesh, India. Recommendations for next steps are discussed, the most important of which is the need for a comprehensive set of formative guidelines for designing locally tailored, culturally appropriate, integrated interventions.